Challenges with seeking HIV care services: perspectives of older adults infected with HIV in western Kenya - Jepchirchir Kiplagat; Ann Mwangi; Charles Chasela; Susann Huschke (BMC, 2019)
Abstract Background While younger adults (15-49 years) form the majority of the population living with HIV, older adults (≥50 years) infected with HIV face multiple challenges related to the aging process and HIV. We explored the experiences of older persons infected with HIV at the Academic Model Providing Access to Healthcare (AMPATH) program in western Kenya to understand the challenges faced when seeking HIV care services. Methods Between November 2016 and April 2017, a total of 57 adults aged 50 years and above were recruited from two AMPATH facilities - one rural and one urban facility. A total of 25 in-depth interviews and four focus group discussions were conducted, audio-recorded, transcribed and thematic analysis performed. Results Study participants raised unique challenges with seeking HIV care that include visits to multiple healthcare providers to manage HIV and comorbidities and as a result impact on their adherence to medication and clinical visits. Challenges with inadequate quality of facilities and poor patient-provider communication were also raised. Participants' preference for matched gender and older age for care providers that serve older patients were identified. Conclusion Results indicate multiple challenges faced by older adults that need attention in ensuring continuous engagement in HIV care. Targeted HIV care for older adults would, therefore, significantly improve their access to and experience of HIV care. Of key importance is the integration of other chronic diseases into HIV care and employing staff that matches the needs of older adults.